Role of exosomes in transforming growth factor-β-mediated cancer cell plasticity and drug resistance - Tatiana Ruksha; Nadezhda Palkina (Exploration of Targeted Anti-tumor Therapy)
Transforming growth factor-β (TGF-β) is a multifunctional molecule with a dual role in carcinogenesis. Recent studies have demonstrated its various effects on cancer-related processes. However, the identification of TGF-β and TGF-β signaling pathway regulators in extracellular vesicles (EVs) appears promising for targeting them to control cancer progression associated with drug resistance. Exosomal TGF-β has been shown to be implicated in cancer cell phenotypic plasticity, a dynamic feature of cancer cells, and an evasive process hampering treatment efficacy. Additionally, EVs can influence the metastatic cascade through mechanisms, including their effects on the immune system and their binding to extracellular matrix (ECM) proteins. These processes collaborate to provide a supportive microenvironment for the development and growth of metastatic tumors. A deeper understanding of the mechanisms by which EVs facilitate TGF-β-mediated intercellular communication may have practical implications for better controlling oncological disorders and providing new methods for cancer diagnostics and treatment, including approaches targeting EVs.